The Role of Islamic Education in Building Ecological Awareness Among Youth - Oppi Wulansari; Siti Afifatun (LP3M Pascasarjana STAI Ibnurusyd, 2025)
This study explores the role of Islamic education in building ecological awareness among youth by examining how Islamic values are integrated into the curriculum, pedagogy, and educational strategies in Islamic institutions. Using a qualitative descriptive method, data were collected through literature studies and in-depth interviews with educators and students at Islamic schools and pesantren. The findings show that Islamic teachings contain strong ecological values such as khalifah (stewardship), amanah (responsibility), and ihsan (compassion), which, if effectively taught, can shape youth attitudes toward environmental preservation. However, these values are often not explicitly embedded in the formal curriculum, and the implementation is still limited. The study recommends integrating eco-theological education models into Islamic education to develop more holistic and spiritually grounded ecological consciousness. This approach provides both a moral foundation and practical strategies to support sustainability efforts among Muslim youth.